(untitled) (Olhar de Professor, 2021)
This article reports the experience of three teachers of babies and very young children at the Unidade de Educação Infantil Ipê Amarelo (UEIIA), at the Federal University of Santa Maria (UFSM), at a time of social distancing due to the coronavirus pandemic, in which we question ourselves about how to guarantee children’s rights and how to be supportive of families. In view of this, and knowing the common interests of the babies and the very young children in our class, we have been confident in the creation of mini-stories (FOCHI, 2019). Families have reported contentment in receiving the mini-stories and enjoying them together with babies and very young children. Thus, these writings have shown to be tools that potentialize pleasurable moments of bond strengthening between family members and children (REYES, 2010; PARREIRAS, 2012), as well as being a way of maintaining affectionate memories of classmates, teachers, the UEIIA, and the moments lived there, in addition to helping calm our hearts in the face of the uncertainties that we live today.